An introduction to performance analysis of sport - O'Donoghue, Peter (Routledge studies in sports performance analysis, 2015)
"Performance analysis has become an essential tool for coaches, athletes, sports organisations and academic researchers. Collecting and interpreting performance data enables coaches to improve their training programmes, athletes to make better tactical decisions, sports organisations to manage teams more effectively, and researchers to develop a better understanding of sports performance. This book is an essential introduction to the fundamental principles of performance analysis of sport and how to develop and operate performance analysis systems. Containing worked examples from real sporting events throughout, the book introduces the basics of quantitative and qualitative performance analysis, reviews the different types of data and information that performance analysis can generate, and explains how to test for reliability. It presents a step-by-step guide to developing both manual and computerised analysis systems, and writing up and presenting findings from performance analysis programmes. Representing the most up-to-date, concise and engaging introduction to sports performance analysis, this book is an ideal course text for all introductory performance analysis courses, as well as an invaluable primer for coaches and practitioners in sport"--